ANALISIS PENERAPAN AKUNTANSI PERSEDIAAN BERDASARKAN PSAK NO.14 PADA PT. GATRACO INDAH MANADO - Wullur, Rachel Anly Marilyn Lingkanwene; Karamoy, Herman; Pontoh, Winston (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
Inventories are assets owned by the company that are available for sale or goods that will be used in the production of the company’s product. With inventory, the company can sustain their sustainability. Companies often experienced problems in recording and assessment the inventories itself. Aim to make this observation on PT Gatraco Indah is to determine the suitability on the application of the inventory recording method and inventory valuation method of manufacture inventory in the PT Gatraco Indah with Statement of Financial Accounting Standards (SFAS) 14 about Inventory. PT Gatraco Indah is a company engaged in food and beverages for airline companies in Indonesia, especially in North Sulawesi. The Methods that was used in this research is descriptive research method with qualitative analysis techniques outline, describe and compare the data. The Result of this research shows that the company has applied the PSAK No.14 on their inventories.